మన భాష – 1 - Kasturi Vishwanatham (Central Institute of Indian Languages Mysore, 1973)
Main purpose of this book is to teach basic fundamentals of telugu to non-telugu persons
Apni Boli Teacher's Manuel in Telugu Level 1
Keywords: Telugu; Teacher's Manual; Telugu